Pengembangan Modul Pengenalan Karir untuk Siswa MTs (Jurusan Bimbingan dan Konseling Islam, 2022)
One of the educational environments that play a major role in children's education from an early age is the family environment. Nowadays, the rapid development of technology makes many values ??and norms change, both positive and negative. These changes indirectly require parents to be able to adjust parenting patterns according to the demands of the times. 21st century thinking skills in this case become one of the skills that must be introduced to students from an early age. Responding to the increasingly complex challenges of authoritarian, permissive, and democratic parenting that may have been effective at that time, may no longer be relevant to use in the digital era as it is today. Referring to these conditions, this study aimed to analyze the role of millennial parenting on students' critical thinking skills. This study uses a library research method through qualitative research by reviewing the literature relevant to this topic. The results of the study show that the role of millennial parents' parenting has an impact on shaping 21st century thinking skills.